2015
DOI: 10.1016/j.addbeh.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Influences of behavior and academic problems at school entry on marijuana use transitions during adolescence in an African-American sample

Abstract: Background: The aim of this study was to examine how patterns of academic and behavior problems in first grade relate to longitudinal transitions in marijuana use from middle school through entry into high school among African Americans. Methods: Latent class and latent transition analyses were conducted on a community sample of 458 low-income, urban-dwelling African-Americans. Results: Two behavior problem classes emerged at school entry; externalizing and attention/concentration. Academic problems co-occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Previous research has identified conduct disorder influences transitions to cannabis use opportunity, and from the opportunity to dependence (Hines et al 2016). This is in line with existing research demonstrating the consistent influence of conduct disorder on drug use (Lynskey et al 2002; Storr et al 2011; Reboussin et al 2015), and genes relating to conduct disorder and involvement with deviant peers (Gillespie et al 2009 a ) are plausible candidates for the shared genetic liability between age of opportunity and the development of cannabis abuse/dependence. Additionally, personality factors associated with drug use (Malmberg et al 2010), such as sensation seeking, may underlie this shared genetic liability.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has identified conduct disorder influences transitions to cannabis use opportunity, and from the opportunity to dependence (Hines et al 2016). This is in line with existing research demonstrating the consistent influence of conduct disorder on drug use (Lynskey et al 2002; Storr et al 2011; Reboussin et al 2015), and genes relating to conduct disorder and involvement with deviant peers (Gillespie et al 2009 a ) are plausible candidates for the shared genetic liability between age of opportunity and the development of cannabis abuse/dependence. Additionally, personality factors associated with drug use (Malmberg et al 2010), such as sensation seeking, may underlie this shared genetic liability.…”
Section: Discussionsupporting
confidence: 88%
“…In Chile and the US, males have been found to be slightly more likely than females to have a chance to use cannabis (Caris et al, 2009; Van Etten and Anthony, 1999), but these gender differences have not been consistently observed (Wells et al, 2011). Childhood religious practices are associated with decreased likelihood of cannabis use opportunity (Chen et al, 2004), and those with externalising behaviour problems have been found to be more likely to have a cannabis use opportunity (Neumark et al, 2012; Reboussin et al, 2015). Perhaps unsurprisingly given that first cannabis use opportunity typically occurs in late childhood or early adolescence, lower parental involvement and higher levels of coercive discipline have been found to be associated with increased likelihood of cannabis use opportunity (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of longitudinal studies have found a temporal relationship between earlier delinquent behavior and later marijuana use in adolescence as well as in adulthood (Becker et al 2012; Brook et al 2011; Reboussin et al 2015). For example, Reboussin et al (2015) found that youths who engaged in externalizing behavior were significantly more likely to transition from no marijuana involvement to the use of marijuana using a community sample of 458 low-income, urban-dwelling African Americans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Reboussin et al (2015) found that youths who engaged in externalizing behavior were significantly more likely to transition from no marijuana involvement to the use of marijuana using a community sample of 458 low-income, urban-dwelling African Americans. In contrast, religiousness seemed to have a protective effect on marijuana use.…”
Section: Introductionmentioning
confidence: 99%